Agents of s.h.i.e.l.d. (2016), volume 1 ebook The coulson protocols. - Guggenheim, Marc (Agents of S.H.I.E.L.D. (2016), 2016)
Collects Agents of S.H.I.E.L.D. #1-6 and material from All-New, All-Different Point One #1. The stars of hit TV show MARVEL'S AGENTS OF S.H.I.E.L.D. explore the All-New, All-Different Marvel Universe, rubbing shoulders with heroes like Tony Stark, Spider-Man and Wolverine! Phil Coulson is reunited with his great love, Lola — no, not the flying car — but this old flame has turned his mind into a weapon that could destroy everything! And if they survive, the Agents of S.H.I.E.L.D. will be forced into a STANDOFF against the New Avengers! Fitz risks his life; Simmons battles for hers; May is the cavalry; and Quake, Mockingbird and Deathlok add the super-hero credentials. But are the Agents of S.H.I.E.L.D. ready for Grant Ward?